N-Methylation of isoDGR peptides: discovery of a selective alpha 5 beta 1-integrin ligand as a potent tumor imaging agent - Kapp, Tobias G.; Di Leva, Francesco Saverio; Notni, Johannes; Raeder, Andreas F. B.; Fottner, Maximilian; Reichart, Florian; Reich, Dominik; Wurzer, Alexander; Steiger, Katja; Novellino, Ettore; Marelli, Udaya Kiran; Wester, Hans-Juergen; et al. (Journal of Medicinal Chemistry, 2018)
Specific targeting of the integrin subtype alpha 5 beta 1 possesses high potential in cancer diagnosis and therapy. Through sequential N-methylation, we successfully converted the biselective alpha 5 beta 1/alpha v beta 6 peptide c(phg-isoDGR-k) into a potent peptidic RGD binding aSfil subtype selective ligand c(phg-isoDGR-(NMe)k). Nuclear magnetic resonance spectroscopy and molecular modeling clarified the molecular basis of its improved selectivity profile. To demonstrate its potential in vivo, c(phg-isoDGR-(NMe)k) was trimerized with the chelator TRAP and used as a positron-emission tomography tracer for monitoring alpha 5 beta 1 integrin expression in a M21 mouse xenograft.